IRAK-M Deficiency Exacerbates Ischemic Neurovascular Injuries in Experimental Stroke Mice - Lyu, Chenfei; Zhang, Yongfang; Gu, Minhua; Huang, Yusheng; Liu, Guanghui; Wang, Chen; Li, Miaodan; Chen, Shumin; Pan, Suyue; Gu, Yong (Frontiers in Cellular Neuroscience, 2018)
Abstract Background: Innate immune response to neuronal death is one of key events of the pathogenesis of ischemic brain injury. Interleukin-1 receptor-associated kinase (IRAK)-M, encoded by gene Irak3, negatively regulates toll-like receptor signaling by interacting with MyD88-IRAK-4-IRAK-1 complex and blocking the phosphorylation and dissociation of IRAK-1. Its function in the ischemic stroke is unknown. Objective: This study aims to investigate whether IRAK-M deficiency could exacerbate neuroinflammation and neurovascular injuries during cerebral ischemia and reperfusion. Methods: Male C57BL/6 mice and Irak3 knockout mice were subjected to 45 min of middle cerebral artery occlusion and 4 or 24 hr of reperfusion. Transcription of Irak3 gene was evaluated by quantitative real-time PCR (qRT-PCR). Then, infarct volume, neurological score, brain water content, and Evans blue leakage were compared between knock-out and wild-type mice after reperfusion. Through the observation of gross brain specimen after cerebral ischemia, the incidence of hemorrhage transformation was compared between KO and WT mice. To explore underlying signaling pathways involved in IRAK-M deficiency, major proinflammatory cytokines and NF-κB signaling were measured by qRT-PCR and western blot. Results: The expression of IRAK-M peaked at 1 hr after reperfusion, gradually decreased within the first 24 hr, which was abolished by blocking the expression of hypoxia induced factor 1α. IRAK-M deficiency increased infarct volume, brain edema, the incidence of hemorrhage transformation, and the permeability of blood brain barrier. In addition, the NF-κB-mediated expressions of proinflammatory cytokines and the activation of microglia in the ipsilateral brain from knock-out mice were much higher than those in wild-type littermates. Conclusion: IRAK-M deletion exacerbates neurovascular damages which are related to the pronounced activation of NF-κB signaling and neuroinflammatory responses during cerebral ischemia-reperfusion in mice. Our study indicates that IRAK-M has neuroprotective effect and has potential to facilitate the development of new pharmaceuticals that reduce neurovascular complications.